Validation of the Modena bleeding score in endoscopic sinus surgery - Alicandri-Ciufelli,Matteo (2022)
Abstract Introduction: The Modena bleeding score is a categorical rating scale that allows the assessment of the surgical field in relation to bleeding during endoscopic surgery. It has recently been presented and validated in the field of endoscopic ear surgery by the present authors. The Modena bleeding score provides five grades for rating the surgical field during endoscopic procedures (from grade 1 – no bleeding to grade 5 – bleeding that prevents every surgical procedure except those dedicated to bleeding control). Objective: The aim of this study was to validate the Modena bleeding score in the setting of endoscopic sinus surgery. Methods: Fifteen three-minute videos of endoscopic sinus surgery procedures (each containing three bleeding situations) were evaluated by 15 specialists, using the Modena bleeding score. Intra and inter-rater reliability were assessed, and the clinical validity of the Modena bleeding score was calculated using a referent standard. Results: The data analysis showed an intra-rater reliability ranging from 0.6336 to 0.861. The inter-rater reliability ranged from 0.676 to 0.844. The clinical validity was α = 0.70; confidence limits: 0.64 – 0.75, corresponding to substantial agreement. Conclusion: The Modena bleeding score is an effective method to score bleeding during endoscopic sinus surgery. Its application in future research could facilitate the performance and efficacy assessment of surgical techniques, materials or devices aimed to bleeding control during endoscopic sinus surgery.